The Effects of Acute Dehydration on Some Physical, Physiological and Performance Parameters in Elite Wrestlers - Samet KIZILKAN; Ahmet MOR (ümit doğan üstün, 2023)
The aim of this study was to investigate the effects of acute fluid loss on some physical, physiological and performance parameters in wrestlers. Active and trained 24 male wrestlers, aged 18-22, voluntarily participated in this study. Participants were randomly divided into two groups as experimental (n=12) and control (n=12). While the experimental group was given weight loss training, normal training was applied to the control group. The effects of acute fluid loss were investigated by applying body hydration level, reaction time, vertical jump, claw strength and balance tests before and after training. Intragroup comparisons were analyzed with dependent sample t-test; intergroup comparisons were analyzed with independent sample t-test. In the study, statistically significant differences were found in favor of the control group in balance and hand grip strength in group comparisons (p<0.05). In addition, it was determined that there was a statistically significant difference in favor of the control group in rating of perceived exertion (RPE) levels (p<0.05). Although there were significant differences in reaction time, the values of the two groups show similarity (p<0.05). Accordingly, there was a difference in favor of the control group in balance and hand grip strength performances. However, the experimental group perceived the difficulty of the training at a higher level. Compared to the control group, these negative effects in the experimental group may have resulted from dehydration. This result shows that the wrestlers are not affected much in terms of physical performance after weight loss training, but they are negatively affected psychologically, and this suggests that rapid weight loss may have a negative effect on match performance.